Impact of Human Activities on the Hydrological Cycle: A Regional Climate Change Case Study - Pierce, David W; Barnett, Tin P (Annals of Arid Zone, 2016)
Evidence of human inducedchangeshas been foundÂ  in many of the Earth'sfundamental hydroclimatic fields, such as temperature and precipitation. Here we take one example of such large-scale changes and follow them through a series of impacts down to specific regional and local consequences.We use as our test case changes in the climate of the western United States,and what these changesimply for water deliveriesfrom the Colorado River. Human induced changes in the hydrologicalcycle of the western United States have recentlybeen demonstratedwithvery high statisticalsignificance.Thesechangesare downscaled and the high resolution environmental data that results are used to drive a hydrological model of the region. The hydrological implications of the changes are used along with a water budget model of the Colorado System to estimate changes in water available for delivery to farms, commercialactivity,and urban cel1tersinto the future. We find the current Colorado water deliveries are not sustainable in the face of human-induced climate change, with major shortages expected only 15-20years into the future. Other regions of the world are also predicted by global climate models to have water problems in the near futu~e. The procedures used here can be a template for estimatingdetailed impacts on water supplIes in these regions. Key words: Climatechange, detectionand attribution,hydrologicalmodeling,ColoradoRiver